Revitalisasi Metode Tilawati dalam Mengatasi Kesulitan Membaca Al-Qur’an pada Siswa MI Guppi Bangunsari - Pratama, Marsel Gusti; Alwi, Itsnaini Muslimati (ARZUSIN, 2025)
This study is motivated by the limited research on the effectiveness of the Tilawati method in improving the reading skills of students in madrasah ibtidaiyah, despite the fact that this phenomenon has a significant impact on achieving the learning objectives of Islamic Religious Education. The objective of this research is to describe the process of applying the Tilawati method and to analyze its effectiveness in improving students' reading skills in the Al-Qur’an. The method used is descriptive qualitative, with a sample of two classes (Class III and IV) selected through purposive sampling techniques. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed using thematic analysis techniques. The results indicate that the Tilawati method has been proven to enhance students' fluency and accuracy in reading the Al-Qur’an, although its implementation still faces challenges such as limited supporting media and teacher training. These findings align with the research objectives and strengthen the theory of individual classical learning that emphasizes habituation and repetitive skills. The main conclusion of this study is the importance of a structured and interactive role of the Tilawati method in reading instruction for the Al-Qur’an. The implications of this research include theoretical aspects, namely enriching the literature on Al-Qur’an learning methods, as well as practical aspects, providing recommendations for teachers and Islamic educational institutions to strengthen the training of the Tilawati method and the provision of adequate learning media. This study also opens opportunities for further research on the integration of the Tilawati method with digital technology in Al-Qur’an learning.